Constructing Philosophy 0f Accounting: Focusing on Axiology - Sukoharsono, Eko Ganis (Accounting Department,, 2023)
Purpose - The objective of this study is to construct a philosophy of accounting derived from the analysis of the spiritualist paradigm. The study aims to utilize an interpretive paradigm to build a foundational understanding of accounting based on philosophical assumptions. Methodology - This research adopts an interpretive paradigm to explore the philosophical foundations of accounting. The study involves a theoretical analysis, synthesizing various philosophical perspectives, with a focus on the spiritualist paradigm. The methodology emphasizes understanding the axiological (value-based) dimensions of accounting, including ethical, moral, cultural, and stakeholder-related aspects. Findings - The study reveals that the philosophy of accounting is constructed around axiology, emphasizing a holistic approach that integrates ethics, moral values, stakeholder interests, and cultural values. The philosophy of accounting is understood as not just a technical or financial discipline, but one that incorporates a broader ethical and value-based perspective. Practical Implication - The findings suggest that a philosophical approach to accounting can guide the development of accounting practices that are more ethically and culturally aware. This approach can help inform policy-making, educational frameworks, and corporate social responsibility initiatives, ensuring that accounting practices align with ethical, moral, and cultural considerations. Original Value - This study offers a novel contribution to accounting theory by constructing a philosophy of accounting rooted in the spiritualist paradigm. It goes beyond traditional technical views of accounting, providing a value-driven, holistic perspective that includes ethics, stakeholder concerns, and cultural influences.